De la jachère à la culture continue - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
La jachère en Afrique tropicale. De la jachère à la jachère améliorée. Le point des connaissances. Volume 2. Ch. Floret et R.Pontanier. Coédition John Libbey Eurotext, CE, CORAF, CTA et IRD, 2001. 355 pages, ISBN 2-7420-0302-9. N° CTA 1035.